INFLUENCE OF LARGE WOODY DEBRIS ACCUMULATIONS ON MACROINVERTEBRATE DISTRIBUTION IN A LOW ORDER FORESTED TROPICAL STREAM, SAGANA RIVER, KENYA - Mwangi, Benson M.; Odhiambo, C. (Jomo Kenyatta University of Agriculture and Technology, 2014)
Woody debris accumulations are important ecological components in low order forested streams. They provide forage and refuge for a macroinvertebrates, which are key trophic components for riverine fish. The occurrence of woody debris in tropical streams is however threatened by large scale destruction of catchment forests thereby threatening the riverine biodiversity. Despite their importance, the current status of woody debris accumulations in tropical forested streams is unknown. In this study we determined the densities of debris dams in a forested stream section, their effectiveness in coarse particulate organic matter (CPOM) retention and the associated macroinvertebrates along a 100m stream stretch within the mid‐reaches of Sagana River. Volume of woody debris was estimated from length, width and height. All components retained were collected, sorted and dried to a constant weight at 85oC. Prior to drying of the organic matter, macroinvertebrates in the CPOM were picked, sorted into different taxa and enumerated. The average density over the whole study period was 2 woody debris dam accumulations per 100m stream stretch. The macroinvertebrates occurring at the debris dams were dominated by Coleoptera (47.3%), followed by Diptera (22.7%) and Ephemeroptera (19.2%). The Coleoptera were dominated by Gyrinidae, Elmidae and Scirtidae. Woody debris play an important role as long‐term retention structures for organic matter and food resources. They forms an important component of riverine ecosystems with regard to CPOM retention, macroinvertebrates distribution and abundance which are indicators of habitat condition. There is therefore need for re‐introductions of such structures for effective channel restoration. We recommend maintenance of buffer strips of riparian vegetation along river banks to protect riverine communities from adverse effects of land‐use changes within Mt. Kenya catchment region.
Keywords: Debris dams; macroinvertebrates; organic matter; streams